Javanese Maxims as Politeness Guidance in Social Media Phatic Communication: A Cyberpragmatics Perspective - Yuli Widiana (Javanologi: International Journal of Javanese Studies, 2023)
Communication on social media raises at a significant rate during the Covid-19 Pandemic. Social media communication (SMC) in specific culture requires particular strategies related to cultural norms. Due to the limitation of cyber communication compares to direct communication, users of social media utilize available features in social media platforms to perform politeness. The strategies of Javanese netizens to perform Javanese politeness maxims in SMC are the main discussion in this study. The data were collected from five WhatsApp Groups (WAG) of Javanese adults of 20s-40s of age comprising 246 respondents. The conversation texts containing phatic talks in WAG were selected by observation method. Then, the conversational texts and communication icons were transcribed for contextual analysis. The result shows that the Javanese maxims of Kurmat (Respect), Tepa Selira (Tolerance), Andhap Asor (Humility), and Empan Papan (Self-Awareness) were utilized by Javanese netizens in performing politeness in virtual phatic communication. During the pandemic, tolerance maxim is the most frequently used to support each other. The maxim of humility is not obvious in virtual phatic communication. To this extent, Javanese politeness maxims are mitigating devices to establish social rapport in phatic communication. The Javanese ability in performing Javanese maxims as politeness devices is essential to avoid conflict and mitigate Face Threatening Act (FTA) since the Javanese community tends to create harmony in life known as Guyub Rukun.